2020
DOI: 10.1371/journal.pone.0231211
|View full text |Cite
|
Sign up to set email alerts
|

“When you first walk out the gates…where do [you] go?”: Barriers and opportunities to achieving continuity of health care at the time of release from a provincial jail in Ontario

Abstract: We aimed to explore continuity of health care and health barriers, facilitators, and opportunities for people at the time of release from a provincial correctional facility in Ontario, Canada. We conducted focus groups in community-based organizations in a city in Ontario, Canada: a men's homeless shelter, a mental health service organization, and a social service agency with programs for people with substance use disorders. We included adults who spoke English well enough to participate in the discussion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…The barriers to continuity of care identified by providers, including disruptions to patientprovider relationships, medication access and health insurance coverage, align well with findings from previous research that explored experiences of individuals recently released from incarceration, as well as physicians who work in jail or prison settings [22][23][24][25]. Such disruptions to care may contribute to poor health outcomes and an increased risk of recidivism.…”
Section: Discussionsupporting
confidence: 67%
“…The barriers to continuity of care identified by providers, including disruptions to patientprovider relationships, medication access and health insurance coverage, align well with findings from previous research that explored experiences of individuals recently released from incarceration, as well as physicians who work in jail or prison settings [22][23][24][25]. Such disruptions to care may contribute to poor health outcomes and an increased risk of recidivism.…”
Section: Discussionsupporting
confidence: 67%
“…There is a growing body of evidence on successful transitional programs to engage patients with healthcare services after release—mainly conducted by community-based providers and NGOs—ranging from reminder calls to intensive case management [ 43 ]. Three studies from the USA have reported that only one-quarter of patients who returned to the community were linked to HCV care after incarceration [ 15 , 30 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…These factors would differ while in prison and in the community: in the community, housing, family responsibilities, and substance use may play a bigger role, and in prison, women may need to deal with medical issues, such as withdrawal, and logistical issues, such as court attendance and challenges in accessing health care. 24 In addition, the time around imprisonment may represent a period of increased challenges for women who experience imprisonment, for example, related to illicit drug use, which may lead to imprisonment itself in the context of criminalization and could also be associated with less antenatal care. This issue could further explain the difference between prison pregnancies and prison control pregnancies (ie, worse antenatal care use for women during prison pregnancies may be associated in part with a challenging period in women’s lives as well as with imprisonment itself).…”
Section: Discussionmentioning
confidence: 99%